Head and neck immunoglobulin G4 related disease: systematic review. Issue 12 (18th December 2018) - Tirelli, G; Gardenal, N; Gatto, A; Quatela, E; Del Piero, G C
Abstract: Background: Immunoglobulin G4 related disease is a recently described systemic syndrome. The head and neck region is the second most common site for presentation after the pancreas. Methods: PubMed and the Cochrane Library were searched from 1995 to July 2017 for all the studies on immunoglobulin G4 related disease diagnosed in the head and neck compartment. Patient-specific data were extracted and basic statistical analysis was performed. Results: Ninety-one patients were identified. Treatment was specified in 76 patients. Twenty patients received surgical treatment, eight of them in association with medical therapy. Fifty-six patients received medical treatment. The disease recurred in 25 per cent of patients treated with surgical treatment alone, in 3.6 per cent of patients treated with medical treatment alone and in 12.5 per cent of patients treated with both. All medical treatment protocols contained high-dose corticosteroids. Conclusion: Early and correct diagnosis can avoid unnecessary surgical treatment, and glucocorticoid therapy can improve the long-term prognosis.